Effective Strategies in Learning English for Generation Z in the Digital Era - Fajarwati, Neni Desi (Journal Corner of Education, Linguistics, and Literature, 2025)
Educational transformation in the digital era demands learning strategies that can meet the needs of Generation Z students who have critical, collaborative, and technologically literate characteristics. This study aims to examine digital, collaborative, and contextual-based English learning strategies that are relevant in improving the communicative skills of Generation Z students. The method used is a literature study, by reviewing the results of previous studies related to the use of digital media, collaborative approaches, and contextual learning in English teaching. The results of the study indicate that the use of digital platforms such as Quizziz, YouTube, and Wordwall can increase student motivation and learning engagement, while role-play methods, group discussions, and project-based learning are effective in fostering students' self-confidence, creativity, and active speaking and writing skills. In conclusion, learning strategies that integrate digital, collaborative, and contextual approaches are very suitable for the characteristics of Generation Z and can create a meaningful, interactive, and enjoyable English learning process in madrasas.